2022
DOI: 10.1177/00207640221093495
|View full text |Cite
|
Sign up to set email alerts
|

Perceived public stigma and perceived public exposure by persons living with bipolar disorder: A qualitative study

Abstract: Background: Stigma impact the lives of persons living with bipolar disorder. Aim: The aim of this study was to explore how perceived public stigma is described by people living with bipolar disorder and examine the links between perceived public stigma and perceived public exposure. Method: Face-to-face in-depth interviews were conducted in a purposive sample of euthymic people living with bipolar disorder recruited in a mood disorder ambulatory unit. Results: Thematic analysis of the transcript yielded five i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…The analysis of available studies revealed that many factors could effectively predict stigma in people living with bipolar disorders and their families, including social and cultural structures, inefficient welfare system, low education, unemployment or lack of a suitable job, low self-esteem, poor communication skills, lack of intimate relationships with others, lack of being understood by others, poor social support, collectivist cultures, young age at disease onset, recurrent hospitalizations, gender, disease severity, disease duration, discriminative labels, lack of information/knowledge, generalization, banalization and reaction induced by public stigma in the general population, or among professionals such as health care professionals and employers. This finding was consistent with the results of Bonnington, Clemente, Favre, Sadeghi, Engidaw, Shumet, Thome, Cerit, Sarisoy, Howland, Ellison, Nilsson and Pal (Bonnington & Rose 2014 ; Clemente et al 2017 ; Favre et al 2022 ; Sadeghi et al 2003 ; Engidaw et al 2020 ; Shumet et al 2021 ; Thomé et al 2012 ; Cerit et al 2012 ; Sarısoy et al 2013 ; Howland et al 2016 ; Ellison et al 2015 ; Nilsson et al 2016 ; Pal 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of available studies revealed that many factors could effectively predict stigma in people living with bipolar disorders and their families, including social and cultural structures, inefficient welfare system, low education, unemployment or lack of a suitable job, low self-esteem, poor communication skills, lack of intimate relationships with others, lack of being understood by others, poor social support, collectivist cultures, young age at disease onset, recurrent hospitalizations, gender, disease severity, disease duration, discriminative labels, lack of information/knowledge, generalization, banalization and reaction induced by public stigma in the general population, or among professionals such as health care professionals and employers. This finding was consistent with the results of Bonnington, Clemente, Favre, Sadeghi, Engidaw, Shumet, Thome, Cerit, Sarisoy, Howland, Ellison, Nilsson and Pal (Bonnington & Rose 2014 ; Clemente et al 2017 ; Favre et al 2022 ; Sadeghi et al 2003 ; Engidaw et al 2020 ; Shumet et al 2021 ; Thomé et al 2012 ; Cerit et al 2012 ; Sarısoy et al 2013 ; Howland et al 2016 ; Ellison et al 2015 ; Nilsson et al 2016 ; Pal 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Public figures have disclosed their personal struggles with mental illness, different movies were made, different books were written, and social media also promoted ideas about mental illness. However, in a qualitative study, persons with BD reported that the effects of stigma remained and were experienced as more "insidious" after these attempts to create destigmatization via media or celebrities' disclosure of living with the condition (Favre et al, 2022).…”
Section: Campaigns and Media Efficacy?mentioning
confidence: 99%
“…People living with BD often experience public stigma via newspapers, films/TV series, and celebrity self-disclosure [31]. In patients with BD, perceived stigma is as high as in people with schizophrenia [32], and is associated with worse medication adherence [32].…”
Section: Introductionmentioning
confidence: 99%